1977
DOI: 10.3168/jds.s0022-0302(77)83928-3
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Polyunsaturated Vegetable Oils to Lactating Cows

Abstract: Holstein cows fed concentrate:hay diets also were fed for 14 days supplements of soybean oil plus casein, soybean oil protected from ruminal hydrogenation by encapsulation in a casein-formaldehyde matrix, cottonseed oil plus casein, or cottonseed oil protected with casein formaldehyde. The supplements were fed at rates to give a linoleic acid (18:2) intake of 225 g/day. Yields of milk and milk protein were not affected by treatment. Milk 18:2 was not increased by the unprotected soybean oil or cottonseed oil b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

1979
1979
1991
1991

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…However, when a concentrate containing 87-5 g added tallow per kg was compared with one containing 20 g added tallow per kg, milk yield was non-significantly increased by 50 g/kg (Murphy and Gleeson, 1979a). The normally poor response to high levels of unprotected fat (Storry et al, 1974;Goering et al, 1977) may be related to the decline in digestibility, especially that of fibre, and also to a decrease in forage intake, as found in the present experiment. This theory is supported by the results of the current trial where the inclusion of 104 g unprotected tallow per kg concentrate gave a response of only 33 g/kg milk yield.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…However, when a concentrate containing 87-5 g added tallow per kg was compared with one containing 20 g added tallow per kg, milk yield was non-significantly increased by 50 g/kg (Murphy and Gleeson, 1979a). The normally poor response to high levels of unprotected fat (Storry et al, 1974;Goering et al, 1977) may be related to the decline in digestibility, especially that of fibre, and also to a decrease in forage intake, as found in the present experiment. This theory is supported by the results of the current trial where the inclusion of 104 g unprotected tallow per kg concentrate gave a response of only 33 g/kg milk yield.…”
Section: Discussionsupporting
confidence: 48%
“…Generally the inclusion of high concentrations (up to 100 g per kg) of unprotected fat in the concentrate portion of the diet has not increased the yield of milk or milk fat (Storry, Brumby, Hall and Johnson, 1974;Goering, Wrenn, Edmondson, Weyant, Wood and Bitman, 1977;Murphy and Gleeson, 1979a). Generally the inclusion of high concentrations (up to 100 g per kg) of unprotected fat in the concentrate portion of the diet has not increased the yield of milk or milk fat (Storry, Brumby, Hall and Johnson, 1974;Goering, Wrenn, Edmondson, Weyant, Wood and Bitman, 1977;Murphy and Gleeson, 1979a).…”
Section: Introductionmentioning
confidence: 99%
“…Storry (1970Storry ( , 1973 found a decrease in the acetate : propionate ratio in the rumen. Other studies have shown little or no change in rumen VFA because of feeding unsaturated oils (Steele et al, 1971;Goering et al, 1976). Saturated FA, however, are less digestible than are unsaturated FA in the small intestine (Bayley and Lewis, 1955;Steele and Moore, 1968;.…”
Section: Plant Fatsmentioning
confidence: 99%
“…Oils. Some studies indicate that fats, mainly unsaturated oils, depress milk fat percentage (Pan, 1972;Storry et al, 1973Storry et al, , 1974Pennington and Davis, 1975;Goering et al, 1976). Storry (1970) suggested that depression of milk fat is associated with a negative shift in the acetate:propionate ratio in the rumen.…”
Section: Plant Fatsmentioning
confidence: 99%
See 1 more Smart Citation